(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the efficacy of the yeast Saccharomyces boulardii (SB) as an antidiarrheal agent in 100 children with acute diarhoreal illness. Study Design: Analytical observational study. Materials and Methods: Study was conducted From 1st April 2008 31st August 2008, 200 children 6 months to 12 years of age with acute watery diarrhea with duration of less than 07 days without history of fever or blood in stool or severe malnutrition admitted in Paediatric department PMCH were included in the study group. Results: Evaluation of the results showed reduction in the number of stools and an improvement in their consistency in Saccharomyces boulardii group. After 48h and 96h children treated with Saccharomyces boulardii scored better than controls. It is concluded that in Saccharomyces boulardii group significantly more children recovered and normalized stools than controls without adverse reactions. Conclusion: It is concluded from our study that in infant and small children with acute diarrhea treatment with SB achieves significant reduction in the duration of diarrhea and number of stool even in the early period of SB preparation use. This yeast (SB) can be used as an adjunct to oral rehydration in treating acute diarrhea in children.